Implementasi Manajemen Rantai Pasokan Anggrek terhadap Atribut Kualitas Pelayanan dan Produk pada Duta Orchid Sanur, Bali - THALIA RATU ZEFANYA; MADE ANTARA; I MADE SUDARMA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Implementation of the Supply Chain Management of Orchid to Service andProduct Quality Attributtes in Duta Orchid Sanur, Bali. Orchid is one of the potential ornamental plants that are developed because it is popular among the community and is in great demand by consumers. Since 2007 Duta Orchid isone of the best orchid centers in Bali. Seeing these conditions, the authors want to knowabout: (1) Conditions of orchid supply chain management conditions which includechain structure, chain targets, chain management, chain resources and supply chainbusiness processes. (2) Assessments that consumers feel about the quality of serviceattributes and Duta Orchid products that are related to the implementation of orchidsupply chain management.The results of the study show that: (1) Management of theorchid supply chain at Duta Orchid which involves suppliers, orchid agents, florists, andend consumers as a whole runs in an integrated manner as seen from product flow,money flow, and information flow that runs smoothly. (2) An assessment of the serviceand product quality attributes perceived by Duta Orchid consumers is related to theimplementation of supply chain management, the attributes that must be maintained areplant prices, durability, employee friendliness, employee accuracy, complaint handling,service speed, and convenience. transactions, while the attributes that must be improvedare variations in orchids and supporting facilities in the Duta Orchid. Then the last,attributes that have a low priority but still need to be considered are the availability of guarantees, location, plant layout, media promotion, and availability ofinformation.Suggestions that can be used as input for Duta Orchid, namely Duta Orchidmust maintain good and smooth supply chain management. In addition, Duta Orchidshould focus on the attributes in the quadrant I. Another thing is Duta Orchid also needto consider the performance of the attributes located in quadrant III if it can have a goodimpact on Duta Orchid if its performance is improved.